Funeral Rites of the Garos: Unveiling Cultural Assimilation Amidst Christian Influence - R. Marak, Silba; Sharma, Dwijen (Journal of Contemporary Rituals and Traditions, 2023)
This paper analyzes the funeral rites and ritualistic practices associated with death among the Garo community of Northeast India, a community that has undergone linguistic divisions and witnessed fragmentation due to colonialism and subsequent conversion to Christianity. Employing an ethnographic approach, this research meticulously examines funeral rituals and practices through engaged participant observation, comprehensive interviews, and meticulous document analysis. Qualitative analysis reveals distinct patterns and themes, casting a revealing spotlight on the symbiotic relationship that exists between tradition and Christianity. The study finds that the Christian Garos have retained social customs such as matrilineality and the kinship system. However, a noticeable departure from their indigenous animistic belief system has taken place, with numerous deities being replaced by a single God, and fundamental beliefs like life after death seemingly abandoned. Nevertheless, upon closer examination of funeral rites, certain traditional elements are found to persist, reflecting the complex cultural assimilation within the emerging Christian identity among the Garo people. The primary contribution of this research lies in uncovering how these remnants of tradition persist, despite the transformative impact of Christianity on the religious and cultural landscape of the Garo community.